2011
DOI: 10.1515/jpem.2011.092
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric 25-hydroxyvitamin D concentrationsin neurofibromatosis type 1

Abstract: Objective Low 25-hydroxyvitamin D (25OHD) concentrations have been associated with tumors and osteopenia/fractures in adults with neurofibromatosis type 1 (NF1). We report 25OHD concentrations in 109 children with NF1 and 218 age, sex, geographic location, and time-of-year matched controls. Methods Children with NF1 were recruited (n=109; 2–17yr), and clinical data and dual energy x-ray absorptiometry measurements obtained. 25OHD concentrations were measured in subjects and controls. Results More NF1 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
3
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 35 publications
2
37
3
4
Order By: Relevance
“…For example, the average serum concentration of 25-hydroxy-vitamin D (25OHD), which plays a key role in bone metabolism and modulates the absorption of dietary calcium and phosphorus, is lower in NF1 patients than in individuals without NF1,4 and the incidence of fractures has been found to be higher than in siblings and spouses without NF1 5. Low 25OHD concentrations have been associated with tumours and osteopenia or fractures in adults with NF1.…”
Section: Phenotypic Variability In Nf1mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the average serum concentration of 25-hydroxy-vitamin D (25OHD), which plays a key role in bone metabolism and modulates the absorption of dietary calcium and phosphorus, is lower in NF1 patients than in individuals without NF1,4 and the incidence of fractures has been found to be higher than in siblings and spouses without NF1 5. Low 25OHD concentrations have been associated with tumours and osteopenia or fractures in adults with NF1.…”
Section: Phenotypic Variability In Nf1mentioning
confidence: 99%
“…The serum 25OHD concentration has been found to correlate negatively with the number of dermal neurofibromas in NF1 patients 6. Another study showed low 25OHD concentrations in the majority of children with NF1, potentially because of increased pigmentation and/or decreased sunlight exposure 5. However, low 25OHD concentrations in children were not associated with neurofibromas, and 25OHD levels did not correlate with bone mineral density.…”
Section: Phenotypic Variability In Nf1mentioning
confidence: 99%
“…One could even conclude that both the Armstrong et al and the Hockett et al data substantiate the inverse relation of NF1 serum calcidiol and cutaneous neurofibromas. I would suggest that this is the correct conclusion and, as concluded by Stevenson et al [15] age is an important variable. A second reason for not relying solely on low serum calcidiol in NF1 is that calcidiol is only one component in a very complex biochemical schema.…”
Section: Vitamin D and Nf1: Prologuementioning
confidence: 74%
“…However, since low serum calcidiol among persons with NF1 appears to have been confirmed, for example, by Stevenson et al [15] I am puzzled. One of humanity's most important nutrient hormones is deranged in one of humanity's most common genetic disorders and yet NF1 clinicians and investigators seem to settle for both an incomplete characterization of the "deficiency" (e.g., where do calcitriol and the VDR fit in?)…”
Section: Vitamin D and Nf1: Prologuementioning
confidence: 96%
“…Çocuk ve erişkinlerden oluşan bir çalışmada kontrollere göre kırık riskinin sırasıyla 3-5 kat arttığı belirtilmiştir (15). D vitamini kemik mineralizasyonunda başlıca düzenleyicidir.…”
Section: Toplam Hasta Sayısı N (%)unclassified